Magical Phenomena in Reality in Rick Riordan’s Percy Jackson and The Olympians: The Lightning Thief - Anik Cahyaning Rahayu; Sudarwati Sudarwati; Susie Chrismalia Garnida (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
This research examines the elements of magical realism, using descriptive qualitative method, a literary genre depicting magic in the modern world, in Rick Riordan's